A Social Approach to Chagas Disease: A First Step to Improve Access to Comprehensive Care - Sanmartino, Mariana (2020)
The aim of this chapter is to provide new insights to the traditional approaches of the problematic of Chagas disease by questioning the hegemonic paradigmatic frameworks through which the topic is traditionally studied and addressed. These questionings and the proposals derived from them are supported on the evidence of an epidemiological change and entail a transformation in the way of understanding the “disease,” the “affected people,” and the diverse actors and scenarios involved in the problematic.